Dingoes at dinnertime - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2000)
The magic tree house whisks Jack and Annie away to Australia where they must save some animals from a wildfire.
The Last Gift -- Sleepyhead -- Big Foot -- Joey -- Wildfire! -- Hand to Hand -- Rain, Rain, Rain -- The Rainbow Serpent -- What Boy? -- Dreamtime.
"A stepping stone book."
Accelerated Reader AR
Accelerated Reader
Reading Counts
106819
Keywords: Magic -- Juvenile fiction; Animal rescue -- Juvenile fiction; Fires -- Juvenile fiction; Fantasy -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Adventure stories; Droughts -- Juvenile fiction; Zoology -- Australia -- Juvenile fiction; Space and time -- Juvenile fiction; JUVENILE FICTION -- Animals -- Mammals; JUVENILE FICTION -- People & Places -- Australia & Oceania; JUVENILE FICTION -- Reader -- Chapter Books; Australia -- Juvenile fiction; Australia -- Fiction; Accelerated readers; Fiction; Fantasy fiction